ANTI-INFECTIVE POTENTIAL OF A MEDICINAL PLANT PIMPENELLA STEWARTII USED TRADITIONALLY IN HAZARA - Gul, Farzana; Hassan, Mukhtiar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Medicinal plants have been used since long as folk medicines and also in Ayuvedic and Unani systems of treatment. They have importance to save human and animal lives because of their utilization in the herbal medicines. In all over the word plants are in constant use for curing of various kinds of diseases. The herbal medicines are effective due to presence of bioactive compounds along with vitamins and minerals in them. Moreover, plants produce photo-chemicals mainly secondary metabolites which have significant pharmaceutical activities like antioxidant, antimicrobial, pesticidal and anti-tumour activity. They are very effective and have little or no side effects. Methods: Five microbial strains including three fungal and two bacterial species were tested for the efficacy of plant materials by Agar diffusion method. The fungal species were Aspergilus flavus, Aspergilus niger and Alternaria alternata while bacterial species included Arvenia caratovora and Xanthomans spp. Results: Results obtained for methanolic extracts of Pimpenella stewartii against Aspergilus flavus, Aspergilus niger and Alternaria alternata showed significant antifungal activity. The antibacterial screening of Methanolic extracts of Pimpenella stewartii were evaluated against Arvenia caratovora and Xanthomans spp. The best zone of inhibition was found against Xanthomans spp (97.33±2 mm) at 250 ppm concentration followed by Arvenia caratovora (49.7±14 mm) at same concentration. Keywords: Pimpenella stewartii, Aspergillus niger, Xanthomans spp, Methanolic extract